Survey on Self Esteem of Girl Students In District Rohtak: The Impact of Family Size and Parental Behavior on the Academic Motivation and Self-Esteem of Girl Students in District Rohtak (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The students from small families had higher academic motivation thanthose from large families. Academic motivation correlated significantly withmother’s behavior on the dimension of acceptance rejection but not withfather’s behaviour on the same dimension. On the dimensions of fosteringindependence fostering achievement non-achievement parent’s behaviour did notshow any relationship with student’s academic motivation. Gupta (1982) hasshown that father’s profession did not bear any influence on readingperformance. Rani (1980) found that the academic achievement of the studentswas positively related to reflected self-esteem of two other significantfactors (teachers and peers) in the educational set- up for the SC students.She also observed that SC students tend to exhibit significantly bettereducational, social, health adjustments.